MAKNA AKULAH ROTI HIDUP BERDASARKAN YOHANES 6:48-51 - Gulo, Raymond; Yaaro (Sekolah Tinggi Teologi Duta Panisal, 2024)
Jesus revealed Himself as the Bread of life to all mankind. The Bread of Life given by Jesus Christ in the Gospel of John is a place for humans to reach their true end goal. Because the Bread of life revealed by Jesus Christ is the source of life, which can provide happiness, truth, and salvation to all humans. The Bread of Life revealed by Jesus Christ is not just for a while, but for eternity or referred to as eternal. Therefore, to recognize and understand the meaning of John 6:48-51 and get its spiritual meaning. This research is the result of extracting the biblical text using the 4 layers of biblical meaning exegesis method which consists of sarcic, noetic, psychic, and anagogic. Thus, the results of this study provide an understanding that, Jesus Christ is the Bread of life who gives Himself as the source of human life that is always there until forever.